2018
DOI: 10.3390/cancers10020036
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies for Pancreatic Cancer

Abstract: Pancreatic cancer is the third leading cause of cancer related death and by 2030, it will be second only to lung cancer. We have seen tremendous advances in therapies for lung cancer as well as other solid tumors using a molecular targeted approach but our progress in treating pancreatic cancer has been incremental with median overall survival remaining less than one year. There is an urgent need for improved therapies with better efficacy and less toxicity. Small molecule inhibitors, monoclonal antibodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 67 publications
2
50
0
2
Order By: Relevance
“…Haas et al reported no significant difference in overall survival for KRAS wild-type vs. mutant patients, and KRAS mutation status is predictive rather than prognostic in advanced PC (34). Efforts focused on targeting PC have been disappointing (7,36), so the standard of care for PC continues to be chemotherapy. However, chemoresistance is a major challenge in the treatment of PC (14,15,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Haas et al reported no significant difference in overall survival for KRAS wild-type vs. mutant patients, and KRAS mutation status is predictive rather than prognostic in advanced PC (34). Efforts focused on targeting PC have been disappointing (7,36), so the standard of care for PC continues to be chemotherapy. However, chemoresistance is a major challenge in the treatment of PC (14,15,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Amanam and Chung systematically investigated all currently available targeted therapies and drug targets for pancreatic cancer [47]. Many studies have reported HER2 overexpression in up to 45% of patients with PDAC [48].…”
Section: Targets Accordance Comparison Between Clinical Drug Treatmenmentioning
confidence: 99%
“…Targeting specific mutations in pancreatic cancer has been a matter of research for over several decades now. The difficulties and obstacles that have been encountered during multiple therapeutic approaches to the RAS/RAF/MEK/ERK pathway are exemplarily on the so far fruitless way to an effective, personalized treatment [51]. Although more than 90% of PDACs harbour a KRAS mutation, inhibition of RAS activation or its' downstream signalling with farnesyltransferase inhibitors (tipifarnib), MEK 1/2 inhibitors (selumetinib, trametinib) alone or in combination with EGFR inhibitors (erlotinib) either did not show a significant benefit in survival or were not clinically applicant due to overlapping toxicities of small molecule inhibitors and necessary dose reductions.…”
Section: Molecularly Targeted Therapiesmentioning
confidence: 99%